2019
DOI: 10.1016/j.jstrokecerebrovasdis.2018.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Tirofiban Administered at Different Time Points after Intravenous Thrombolytic Therapy with Alteplase in Patients with Acute Ischemic Stroke

Abstract: Objective: To evaluate the efficacy of tirofiban administered at different time points within 24 hours of intravenous thrombolysis with alteplase in acute ischemic stroke. Methods: Patients who underwent intravenous thrombolysis with alteplase and fulfilled other inclusion criteria were randomly divided into 4 groups according to the time points of tirofiban administration: Group A (2 h), Group B (2-12 h), Group C (12-24 h), and Group D (control). The changes in National Institutes of Health Stroke Scale score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…After screening, 15 RCTs(Randomized Controlled Trials) needed to be evaluated in detail, 2 of which are retrospective studies [6,7]; 1 is a historical controlled study [8], 1 is a post-hoc trend matching analysis study of a randomized clinical trial [9], 6 study designs are not suitable [10][11][12][13][14][15]; 1 study population does not meet the inclusion requirements [16]; 1 with very short follow-up time, and has no 90-day efficacy evaluation [17]. Finally, 3 RCTs were included in our analysis [18][19][20] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After screening, 15 RCTs(Randomized Controlled Trials) needed to be evaluated in detail, 2 of which are retrospective studies [6,7]; 1 is a historical controlled study [8], 1 is a post-hoc trend matching analysis study of a randomized clinical trial [9], 6 study designs are not suitable [10][11][12][13][14][15]; 1 study population does not meet the inclusion requirements [16]; 1 with very short follow-up time, and has no 90-day efficacy evaluation [17]. Finally, 3 RCTs were included in our analysis [18][19][20] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Some of these studies have shown that early use of antiplatelet-aggregation drugs is beneficial to patients. However, previous clinical studies suggested that the early application of antiplatelet-aggregation drugs caused increased risk of cerebral hemorrhage [20]. The current clinical guidelines do not recommend the use of anti-platelet drugs within 24 h after thrombolysis.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In AIS patients receiving EVT, studies have also demonstrated that the use of tirofiban could not increase the proportion of patients with mRS 0–2 at 3 months [ 9 , 10 , 23 30 ]. Studies failed to reach a consensus about whether the efficacy of tirofiban was superior in patients receiving IVT with alteplase [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in the incidence of ICH between the two groups. Several studies have also demonstrated that the combination of tirofiban and other standard cares did not increase the risk of ICH [ 13 , 31 , 33 ]. It can be inferred that the administration of tirofiban instead of dual antiplatelet is relatively safe in AIS patients who had fulfilled the inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%